2006
DOI: 10.1364/oe.14.002323
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Al wire-grids as broadband and high-performance polarizers

Abstract: We have fabricated, characterized and theoretically analyzed the performance of bilayer (or stacked) metallic wire-grids. The samples with 100 nm period were fabricated with extreme-ultraviolet interference lithography. Transmission efficiency over 50% and extinction ratios higher than 40 dB were measured in the visible range with these devices. Simulations using a finite-difference time-domain algorithm are in agreement with the experimental results and show that the transmission spectra are governed by Fabry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 20 publications
(27 reference statements)
2
92
0
Order By: Relevance
“…A reliable, fast, and low-cost process which has the potential to produce robust, homogeneous patterns on areas 0.1m 2 and larger is critical to success in these industries. [1][2][3][4][5][6][7][8][9][10][11][12] Many existing methods currently employed in the production of micropatterns are unsuitable for incorporation into a large area process. Research in areas such as thermal and UV light curing imprint lithography have yielded robust, defect free structures with a resolution as low as 10nm; however, these methods are limited to areas of tens of cm 2 or less.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable, fast, and low-cost process which has the potential to produce robust, homogeneous patterns on areas 0.1m 2 and larger is critical to success in these industries. [1][2][3][4][5][6][7][8][9][10][11][12] Many existing methods currently employed in the production of micropatterns are unsuitable for incorporation into a large area process. Research in areas such as thermal and UV light curing imprint lithography have yielded robust, defect free structures with a resolution as low as 10nm; however, these methods are limited to areas of tens of cm 2 or less.…”
Section: Introductionmentioning
confidence: 99%
“…Although the performance of the WGP is affected by the grating pitch, duty and Al layer thickness and so on 17,22) , we analyzed the effects of Al layer thickness on the performance of the WGP, because the main objective of this research is to demonstrate a simple WGP fabrication method using a GLAD and the pitch and duty of the our master pattern is already xed as 100 nm and 0.4, respectively. To determine the ideal thickness of the Al layer, simulations of the transmittance of p-polarized light and the extinction ratio with four different Al layer thicknesses were performed using DiffractMOD (R-Soft), which is a piece of commercial software based on rigorous coupled wave analysis (RCWA).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that there are differences in the transmission of p-polarized light between theoretical and experimental values. 17,22) It is reasonable to argue that this deviation occurs due to fabrication errors. The area of the optically transparent part, which is the side-wall of the nano-grating in the B-WGPs, is the main parameter that affects transmittance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems much more interesting if a simple subwavelength grating can function as a polarizer, which has been reported in transmission [4,5] , reflection [6] , mold injection [7] , embedded metal wire [8] , and metal wiregrids [9] as broadband polarizers [10,11] . For practical use in optical communication, good extinction ratio and high efficiency with a wide angular bandwidth and a broad wavelength range are needed.…”
mentioning
confidence: 99%